PERAN PSIKOLOGI ORGANISASI DALAM PENGABILAN KEPUTUSAN ETIS DILEMBAGA PENDIDIKAN ISLAM: Studi Kasus Kualitatif di Madrasah Aliyah Daarul Muqimien Tangerang - Ahmad Tontowi Jauhari Tontowi; Mulyawan Safwandy Nugraha (JURNAL KAJIAN ISLAM MODERN, 2026)
Decision making and the enforcement of ethics in Islamic educational institutions are influenced by psychological dynamics and organizational interactions. This study aims to analyze the role of organizational psychology in decision-making processes and ethical practices at Madrasah Aliyah Daarul Muqimien Tangerang. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed using thematic analysis. The findings indicate that participatory decision-making through deliberation, open organizational communication, and exemplary leadership significantly contribute to decision legitimacy and the strengthening of an ethical organizational culture. The integration of organizational psychology principles with Islamic ethical values functions as a mechanism for controlling individual bias and reinforcing collective trust. These findings provide a conceptual contribution to organizational psychology studies within the context of value-based Islamic education management